2024
DOI: 10.1177/2333794x231221935
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Clinical, and Pathologic Backgrounds of Children With X-Linked Alport Syndrome in China: A Monocenter Study

Ding Juan-Juan,
Wang Jia,
Liu Li-Li
et al.

Abstract: Background. Characteristics of X-linked Alport syndrome (XLAS) in a cohort of Chinese children. Methods. This work is a retrospective study covering the clinical information, pathological data, and gene sequencing results of 32 cases with XLAS from 2011 to 2022. Results. Among these 32 patients, the youngest age of onset was 3 months. Renal biopsy was performed on 29 children. The lamellated glomerular basement membrane was observed in 19 children using electron microscopy (65.5%). Of the 26 samples tested, 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Recently, an increasing number of studies have reported gene mutations that causing AS in patients with both steroid-resistant NS and FSGS [12]. In cases where AS coexists with other kidney diseases, patients are prone to misdiagnosis, often as NS, IgA nephropathy, Henoch-Schönlein purpura nephritis, or thin basement membrane nephropathy [9].Clinically, some children with AS may have proteinuria as the initial clinical symptom, but the diagnosis of NS in AS patients is indeed rare. In this study, all 7 AS patients had the disease onset during school age, with NS as the primary clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of studies have reported gene mutations that causing AS in patients with both steroid-resistant NS and FSGS [12]. In cases where AS coexists with other kidney diseases, patients are prone to misdiagnosis, often as NS, IgA nephropathy, Henoch-Schönlein purpura nephritis, or thin basement membrane nephropathy [9].Clinically, some children with AS may have proteinuria as the initial clinical symptom, but the diagnosis of NS in AS patients is indeed rare. In this study, all 7 AS patients had the disease onset during school age, with NS as the primary clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Variant loci were graded for pathogenicity according to the ACMG guidelines [8]. The mutations were classi ed as missense or severe mutations (large deletions, nonsense changes, mutations at the splice donor or acceptor site, and frameshift mutations) [9].…”
Section: Next-generation Sequencing and Sanger Sequencingmentioning
confidence: 99%